Conocimiento materno sobre alimentación complementaria y el estado nutricional del lactante - Rodríguez Ruiz, Hilda (2019)
Correlative descriptive descriptive type research was carried out at the Leoncio Prado Hospital - Huamachuco, 2018; in order to determine the relationship between the level of maternal knowledge about complementary feeding and nutritional status of the infant. The sample consisted of 141 mothers with their respective infants. The data collection was obtained through the following instruments: Survey of knowledge of mothers about complementary feeding and Instrument to assess the nutritional status of the infant. The data obtained were tabulated, processed in SPSS version 23 and presented in single and double entry tables with numerical and percentage frequencies. To determine the relationship between the variables, the Chi square test (x2) was used. The results show that: 61.7porcent of mothers present average level of knowledge about complementary feeding, 33.3 porcent high level and 5 porcent low level. The nutritional status of the infant according to Weight / Age 87.2 porcent have normal weight and 7.1 porcent overweight. According to Size / Age, 61 porcent have normal size and 31.9 porcent have short stature. According to Weight / Height, 85.8 porcent have normal nutritional status and 6.4 porcent obesity. There is a significant relationship between the variables.